Terapi Tawa untuk Menurunkan Stres pada Penderita Hipertensi - Desinta, Sheni; Ramdhani, Neila (Jurnal Psikologi, 2013)
Hypertension is a physical condition that is often connected to negative stress or distress. Stress as psychological, emotional and physical responses to a problem one perceives as a burden because it threats his/her wellbeing. Since stress is related to perception, in addition to medical treatment, it is necessary for people with hypertension also receive non-pharmacology therapy. This research aimed to find out the effectiveness of laughing therapy for decreasing distress and blood pressure of people with hypertension. There were twelve (12) hypertension patients voluntarily becoming the subjects of the research. Laughing therapy with duration of 1 – 2 hours was given to them within 6 meetings for 3 weeks. Stress Scale was utilized to collect the data and the progress of the subjects’ behaviors was observed and recorded by the observant on Observation Sheet. Each subject was also asked to fill Self-observation Sheet. Their blood pressures were measured with sphygmomanometer. The method of interview was used to elaborate the data. The data was analyzed using non-parametric statistical method. The results of the analysis showed that there is significance difference between the experimental group and control group of the subjects in terms of their levels of stress (Z=-2.287; p